Life-course socioeconomic status and lung function in adulthood: a study in the EPIPorto cohort. Issue 3 (10th December 2019) - Rocha, Vânia; Stringhini, Silvia; Henriques, Ana; Falcão, Helena; Barros, Henrique; Fraga, Sílvia
Abstract : Objective: This study aims to investigate the association of life-course socioeconomic status (SES) with lung function during adulthood, by exploring the influence of life-course social mobility and of cumulative exposure to low SES. Methods: Participants were 1458 individuals from EPIPorto study, a population-based cohort of Portuguese adults. The life-course SES was computed using participants' paternal occupation and own occupation, resulting in four patterns: stable high, upward, downward, stable low. A cumulative life-course SES index was also calculated using the participants' paternal occupation, own education and occupation. Lung function during adulthood was assessed with forced expiratory volume in first second (FEV1 ) and forced vital capacity (FVC) percentages predicted (higher percentages are associated with better lung function). Linear regression models were used to estimate beta coefficients and 95% CI for the association of socioeconomic indicators and lung function. Results: Disadvantaged SES from childhood to adulthood was associated with lower lung function (FEV1 :−6.64%, −10.68;−2.60/FVC:−3.77%, −7.45;−0.08), and the greater the socioeconomic disadvantage, the lower the lung function (FEV1 :−2.56%, −3.98;−1.15/FVC:−1.54%, −2.83;−0.24) among men, independently of marital status and behavioural factors. Among women, SES effects were only observed in those experiencing a stable low life-course SES at older ages (−5.15%, −10.20;−0.09). Men experiencing a downward social mobility presented the lowest lung function, but there was attenuation to the null after accounting for marital status and behavioural factors. Conclusion: A life-course disadvantaged SES is an important predictor of lower lung function during adulthood. Downward social mobility was associated with the lowest lung function among men, although this association was mostly explained by behavioural factors.